Exponentially dichotomous difference equations with piecewise constant operator coefficients - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.988.6 We obtain the necessary and sufficient conditions for the exponential dichotomy of solutions of linear difference equations with piecewise constant operator coefficients.